2021
DOI: 10.1364/oe.415534
|View full text |Cite
|
Sign up to set email alerts
|

Generation of watt-level supercontinuum covering 2-6.5 µm in an all-fiber structured infrared nonlinear transmission system

Abstract: We demonstrate a watt-level mid-infrared supercontinuum source, with the spectrum covering the infrared region from 2 to 6.5 µm, in an all-fiber structured laser transmission system. To further improve the SC spectral bandwidth, power and system compactness in the follow-up As2S3 fiber, we theoretically and experimentally explored some knotty problems that would potentially result in the As2S3 fiber end-facet failure and low SC output power during the high-power butt-coupling process and proposed an optimal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Generally, fluoride fibers are always chosen as the firststage fiber in the cascading scheme because of the following excellent properties: 1) high damage threshold; 2) generating SC sources with > 3.5 μm long wavelength edge extending above the ZDW of typical step-index fluoride fibers around 1.5 μm; 3) high output power of up to 30 W [18]. Subsequently, this concept has been proved to be feasible by many experimental results [29,[76][77][78][79][80]. In [29], a MOPA pump laser with a repetition rate of 600 kHz shown in Fig.…”
Section: Pumping Chg Fibers By Cascaded Sc Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, fluoride fibers are always chosen as the firststage fiber in the cascading scheme because of the following excellent properties: 1) high damage threshold; 2) generating SC sources with > 3.5 μm long wavelength edge extending above the ZDW of typical step-index fluoride fibers around 1.5 μm; 3) high output power of up to 30 W [18]. Subsequently, this concept has been proved to be feasible by many experimental results [29,[76][77][78][79][80]. In [29], a MOPA pump laser with a repetition rate of 600 kHz shown in Fig.…”
Section: Pumping Chg Fibers By Cascaded Sc Sourcesmentioning
confidence: 99%
“…Subsequently, this concept has been proved to be feasible by many experimental results [29,[76][77][78][79][80]. In [29], a MOPA pump laser with a repetition rate of 600 kHz shown in Fig. 12a was used to increase the average pump power to several tens of watts from the TDFA.…”
Section: Pumping Chg Fibers By Cascaded Sc Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, Woyessa et al demonstrated a stable and portable MIR SC laser source covering the bandwidth from 1.46-10.46 µm with an average output power of 86.6 mW and a repetition rate of 3 MHz in a fiber cascade comprising of silica, ZBLAN, and chalcogenide fibers pumped by 0.5 ns pulsed Er/Yb-MOPA without any amplifier stages [73]. Yan et al demonstrated a watt-level (1.13 W) MIR SC spanning from 2-6.5 µm in a butt coupled ZBLAN and As 2 S 3 cascaded fiber system pumped by a 1550 nm pulsed DFBL and few stages of thulium-doped fiber amplifier [74]. In 2019, C. R. Petersen et al reported 1.07-7.94 µm MIR SC with an average output power of 41 mW in an all fiber cascade comprising of ZBLAN PCF and Ge 10 As 22 Se 68 PCF taper.…”
Section: A Soft-glass Fibersmentioning
confidence: 99%